Public Government Affairs as an Alternative Mechanism for Handling the COVID-19 Outbreak in Indonesia - Rema Mubarak, Arya; Jasmine Azhima, Chalisa; Pramadiathalla, Muhammad (Lex Scientia Law Review, 2020)
Abstracts : This article discusses the policies that has been taken by the central government and some regional government in regards to the COVID-19 outbreak. Analysis is conducted by observing the disharmony between current policies and authority given by respective laws. The study is based on qualitative method by using literature study from Indonesian law and scientific articles. This article concludes that the policies that has been taken is ineffective because of miscoordination and overlapping of authority. Subsequently, there’s vagueness in using concurrent government affair (urusan pemerintahan konkuren) in the field of health or disaster. Such situation worsened after the COVID-19 outbreak declared as health emergency and unnatural disaster which creates dualism in mechanism for handling the outbreak. Therefore, this article describes the use of general government affair or (urusan pemerintahan umum) as an alternative. By making the President the champion of the top, the redistribution of authority and the simplification of coordination between institutions can occur quickly, so that the policies taken are effective in protecting the right to public health. Keyword : Right to Health, Policy, Authority, Public Government Affairs.